Biomechanical study of internal fixation methods for femoral neck fractures based on Pauwels angle - Wang, Fuyang; Liu, Yuchen; Huo, Yi; Wang, Ziming; Zhang, Jinge; Xu, Minghao; Ma, Kaiming; Wang, Linbao; Lu, Yongtao; Cheng, Liangliang; Zhao, Dewei (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To select the most appropriate internal fixation method based on the Pauwels angle, in order to provide a new concept for clinical accurate treatment of femoral neck fractures (FNFs). Methods: FNFs models of Pauwels30°, 40°, 50° and 60° were created respectively. For Pauwels ≤ 50°, 1, 2 and 3 Cannulated Compression Screws (CCS) and Porous Tantalum Screws (PTS) were used to fix the fracture for the models. For Pauwels 60°, 3CCS and Medial Buttress Plate (MBP) combined with 1, 2 and 3CCS were used to fix the fracture. Based on the results of the finite element (FE) analysis, the biomechanical properties of each model were compared by analyzing and evaluating the following four parameters: maximal stress of the bone (MBS), maximal stress of the implants (MIS), maximal displacement of bone (MBD), interfragmentary motion (IFM). Results: At Pauwels 30°, the larger parameters were found in 1CCS, which was 94.8 MPa (MBS), 307.7 MPa (MIS), 0.86mm (MBD) and 0.36 mm (IFM). In 2CCS group, the parameters were 86.1 MPa (MBS), 254.4 MPa (MIS), 0.73 mm (MBD) and 0.27 mm (IFM), which were similar to those of PTS. At Pauwels 40° and 50°, with the increase of the number of used CCS, accordingly, the parameters decreased. Particularly, the MIS (Pauwels 50°) of 1CCS was 1195.3 MPa, but the other were less than the yield range of the materials. At Pauwels 60°, the MBS of 3CCS group was 128.6Mpa, which had the risk of failure. In 2CCS+MBP group, the parameters were 124.2 MPa (MBS), 602.5 MPa (MIS), 0.75 mm (MBD) and 0.48mm (IFM), The model stability was significantly enhanced after adding MBP. Conclusions: Pauwels type Ⅰ (＜30°) fractures can reduce the number of CCS, and PTS is an appropriate alternative treatment. For Pauwels type Ⅱ fractures (30°~50°), the 3CCS fixation method is still recommended. For Pauwels type Ⅲ fractures (＞50°), it is recommended to add MBP to the medial femoral neck and combine with 2CCS to establish a satisfactory fracture healing environment.